Leeds Institute of Cardiovascular and Metabolic Medicine, University of Leeds/Leeds Teaching Hospitals NHS Trust, LIGHT Laboratories, Clarendon Way - F. Cosentino; P. J. Grant; V. Aboyans; G. J. Bailey; А. Ceriello; V. Delgado; M. Federici; G. Filippatos; D. E. Grobbee; T. В. Hansen; H. V. Huikuri; I. Johansson; et al. (Российский кардиологический журнал)
The Task Force for diabetes, pre-diabetes, and cardiovascular diseases of the European Society of Cardiology (ESC) and the European Association for the Study of Diabetes (EASD)